RAPID ROOM TEMPERATURE LIQUID PHASE SYNTHESIS OF DIETHYL 2-((4-NITROANILINO) METHYLENE)MALONATE - Hernán Valle; Ramalinga Viswanathan Mangalaraja; Bernabé L. Rivas; José Becerra; Selvaraj Naveenraj (Journal of the Chilean Chemical Society, 2018)
Diethyl 2-((4-nitroanilino)methylene)malonate [4-NANM-E] is an important molecule owing to its role of precursor in the multistage synthesis of several quinoline derivatives possessing biological activities such as antiviral, immunosuppressive, anticancer and photoprotector. This molecule is usually synthesized by a nucleophilic vinyl substitution (SNV) between 4-nitroaniline and diethylethoxymethylene malonate (EMA). Although several procedures are available to synthesize 4-NANM-E in liquid phase, more convenient method is necessary to synthesize in less reaction time and at room temperature. In this study, it is demonstrated that equimolar amounts of EMA and 4-nitroaniline dissolved in alcoholic KOH react within a few seconds at room temperature to produce 4-NANM-E which is purified by simple filtration after acidification with aqueous HCl and washing with alcohol. The reaction has the yield varying at the range 45-53% when it occurs in ethanol, 2-propanol, 2-butanol or 2-pentanol. Therefore, this synthesis method is an excellent alternative to produce 4-NANM-E on an industrial scale.